(SERVPERF)تقییم مستوى جودة الخدمات الهاتفیة النقالة بنموذج: دراسة حالة مؤسسة -جیزي - ismail, morad; melahi, rokia (Finance and Business Economies Review, 2017)
The aim of this study is to evaluate the level of quality of services from the point of view of customers provided by the djezzy based on SERVPERF model in its five dimensions of quality (sensitivity, reliability, responsiveness, safety and empathy), in addition to the sixth dimension of The study reached a number of conclusions, the most important of which is that the quality of the services provided has a positive impact on the customers, in addition to the relative importance of each of the six dimensions